A review on food waste disposal approach / Suhaila Abdul Hanan, Ariff Mustafa and Muhammad Zuhairi Ziauddin - Abdul Hanan, Suhaila; Mustafa, Ariff; Ziauddin, Muhammad Zuhairi (UiTM Press, 2021)
A review was undertaken to explore the food waste disposal approach from the year 2014 until 2019. Four databases were used to search for articles related to food waste. 324 articles were reviewed prior to selecting 60 papers for final review. The results showed that apart from the economic loss caused by food waste, its environmental and social impacts also cause preventable damage and public debate. Further analyses showed that there were few approaches to food waste disposal. These food waste disposal trends can be categorised into three categories: 1) donation, 2) price reduction 3) food waste recycling programme. These approaches to food waste management have been introduced effectively in the countries studied. Furthermore, the food waste disposal approach could guide the supermarket and other related organisations to follow. However, the limitation of this study utilised four journal databases accessible to the researchers with specific keywords related to this research. Overall, future studies may use other journal databases and keywords for their findings. Future studies also could utilise the quantitative approach with a survey or qualitative method with an interview to gain more insight into this issue.